2018
DOI: 10.3390/v10120671
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Translation of Viral mRNA in Reovirus-Infected Cells: Progress and Remaining Questions

Abstract: At the end of my doctoral studies, in 1988, I published a review article on the major steps of transcription and translation during the mammalian reovirus multiplication cycle, a topic that still fascinates me 30 years later. It is in the nature of scientific research to generate further questioning as new knowledge emerges. Our understanding of these fascinating viruses thus remains incomplete but it seemed appropriate at this moment to look back and reflect on our progress and most important questions that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 208 publications
0
25
0
Order By: Relevance
“…Viral translation also is enhanced by the reovirus σ3 outer-capsid protein [46]. The σ3 protein binds dsRNA during infection, blocking the activation of protein kinase RNA-activated (PKR), an interferon-induced enzyme that is activated by binding to dsRNA [47].…”
Section: Morphology and Functions Of Reovirus Inclusionsmentioning
confidence: 99%
“…Viral translation also is enhanced by the reovirus σ3 outer-capsid protein [46]. The σ3 protein binds dsRNA during infection, blocking the activation of protein kinase RNA-activated (PKR), an interferon-induced enzyme that is activated by binding to dsRNA [47].…”
Section: Morphology and Functions Of Reovirus Inclusionsmentioning
confidence: 99%
“…The outer capsid is then added, coinciding with the arrest of transcriptional activity. For a detailed review on transcription and translation during the viral multiplication cycle, the reader is referred to a recent review [9].…”
Section: Brief Overview Of Reovirus Multiplication Cyclementioning
confidence: 99%
“…This is exerted through the action of interferon-stimulated factors, mainly due to the action of IFIT proteins [15,16,17,18,19]. Interestingly, it has been reported that part of viral mRNA is devoid of a cap structure late in infection, rather harboring a monophosphate end, although the transient presence of a diphosphorylated end is possible [20,21,22] (for a recent review on reovirus mRNA structure and synthesis, see [9]). Finally, in the related rotavirus, it was more recently shown that a fraction of the RNA is not completely capped, and this seems to be responsible for recognition by the sensor RIG-I [23].…”
Section: Reovirus and The Interferon Signaling Networkmentioning
confidence: 99%
“…Within the cytoplasm, the core is transcriptionally active. The encapsidated RNA-dependent RNA polymerases use each genome segment as a template to produce mRNAs [3]. These mRNAs, which are capped by the viral capping enzymes also present in the particle, are extruded through turrets in the core into the cytoplasm, for translation by host ribosomes.…”
Section: Introductionmentioning
confidence: 99%